1997
DOI: 10.1901/jaba.1997.30-411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reinforcement Choice on Task Responding in Individuals With Developmental Disabilities

Abstract: The effects of reinforcement choice on task performance were examined with 6 individuals who had been diagnosed with severe to profound mental retardation. Five highly preferred items were identified for each participant via stimulus preference assessments. Participants then were exposed to choice and no-choice conditions that were alternated within reversal and multielement designs. During choice sessions, participants were permitted to select between two preferred stimuli contingent on responding. During noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 27 publications
4
51
0
4
Order By: Relevance
“…If the choice can be made as a reinforcer, teachers and clinics should provide an additional strategy to treat individuals with severe and profound disability. Furthermore, these fi ndings show the importance of providing frequent choice opportunities to individuals (Lerman et al, 1997).…”
Section: Identifi Cación De Juegos Como Consecuencias Del Comportamenmentioning
confidence: 82%
See 1 more Smart Citation
“…If the choice can be made as a reinforcer, teachers and clinics should provide an additional strategy to treat individuals with severe and profound disability. Furthermore, these fi ndings show the importance of providing frequent choice opportunities to individuals (Lerman et al, 1997).…”
Section: Identifi Cación De Juegos Como Consecuencias Del Comportamenmentioning
confidence: 82%
“…This procedure could be carried out in future studies (Lerman et al, 1997). Using the Matching procedure most likely made the photos of the games acquire conditioned reinforcement value, as well as adding more reliability to the study, demonstrating the possibility of more control in translational and applied research.…”
Section: Discussionmentioning
confidence: 99%
“…Ao se pensar na consequência social como reforçador condicionado, as consequências sociais poderiam inicialmente ser pareadas com reforçadores primários até elas adquirirem valor reforçador condicionado e depois seriam retirados os reforçadores primários, esse procedimento poderia ser realizado em estudos futuros (Lerman et al, 1997). A utilização do procedimento de Matching, muito provavelmente, fez com que as fotos dos jogos adquirissem valor reforçador condicionado, além de atestar mais confi abilidade ao estudo, demonstrando a possibilidade de mais controle em pesquisas translacionais e aplicadas.…”
Section: Discussionunclassified
“…Se a escolha puder ser estabelecida como um reforçador, professores e clínicos deverão apresentar uma estratégia de tratamento adicional para indivíduos com defi ciências severas e profundas. Adicionalmente, tais descobertas ressaltariam a importância de prover frequentes oportunidades de escolha aos indivíduos (Lerman et al,1997).…”
Section: Identifi Cação De Jogos Como Consequências De Comportamentosunclassified
“…Many studies have assessed the preferences of children with autism and severe or profound developmental delay [1]. Lerman et al [2] found that the opportunity for making a choice appears to be beneficial for these individuals. Romaniuk et al [3] reported that individuals who display challenging behaviours often exhibit these when they are given opportunities to make choices, thus demonstrating a stimulus preference.…”
Section: Introductionmentioning
confidence: 99%